Anti-obesity effect of trans-cinnamic acid on HepG2 cells and HFD-fed mice. (March 2020) - Wang, Zhenyu; Ge, Shenghan; Li, Shiyang; Lin, Huiting; Lin, Shaoling
Abstract: Trans-cinnamic acid (tCA) is a phenylpropenoic acid, which occurs naturally in a number of plants. In this study, the anti-obese effects of tCA were evaluated in oleic acid (OA)-induced HepG2 cells and high fat diet (HFD)-fed mice. The results showed tCA treatment significantly decreased lipid accumulation in HepG2 cells exposed to OA . Furthermore, administration of tCA (40 mg/kg/day) curbed body weight gains, reduced liver and adipose tissue weight, and ameliorated hepatic steatosis and adipose hypertrophy in mice fed with HFD. In addition, significant decrease in plasma levels of TG, TC and LDL-C were also observed in HFD-fed mice with tCA treatment. Collectively, tCA may play a vital role in preventing and treating diet induced obesity. Graphical abstract: A possible association exits between intake of trans-cinnamic acid and amelioration of obesity. The anti-obese action of trans-cinnamic acid was investigated in HepG2 cells and high fat diet (HFD)-induced obese mice. Trans-cinnamic acid effectively reduced body weight gain, liver weight and fat mass in HFD-fed mice, and inhibited hepatic lipid accumulation both in vitro and in vivo . These findings suggested dietary supplementation of trans-cinnamic acid may play beneficial roles in the prevention of obesity. Image 1 Highlights: Trans-cinnamic acid alleviated lipid accumulation in HepG2 cells. Trans-cinnamic acid improved blood lipid profile in high fat diet-induced mice. Trans-cinnamic acid also improved hepatic steatosis and adipose hypertrophy in high fat diet-induced mice.